Activating participation : parents and teachers working towards partnership - Reay, Diane; Crozier, Gill (Trentham Books, 2005)
Participatory democracy at grass roots level is hugely complex, especially in a diverse society. This book seeks to examine this issue in the context of children's education, identifying the key factors that affect parents' participation and what their role should be.